2007
DOI: 10.1177/230949900701500311
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Stabilisation System Plating for Distal Femoral Fractures

Abstract: LISS plating is useful in treating complex distal femoral fractures, resulting in reduced blood loss and low infection rates, while achieving early mobility due to primary stability of the construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 19 publications
2
41
0
3
Order By: Relevance
“…7 Strength under axial compression was better with the LCP system than with the blade plate or nailing, by 34 and 13% respectively, but strength under torsion was reduced. [8][9][10][11][12] The authors observed better distal fixation with the LCP system with loss of distal fixation in only one LCP plate (6%), three blade plates (38%) and eight losses with retrograde intramedullary nailing (100%).…”
Section: Discussionmentioning
confidence: 98%
“…7 Strength under axial compression was better with the LCP system than with the blade plate or nailing, by 34 and 13% respectively, but strength under torsion was reduced. [8][9][10][11][12] The authors observed better distal fixation with the LCP system with loss of distal fixation in only one LCP plate (6%), three blade plates (38%) and eight losses with retrograde intramedullary nailing (100%).…”
Section: Discussionmentioning
confidence: 98%
“…Kanabar et al, 7 in his study noted bone union in a mean period of 17(Range, 10-36) weeks and mean range of knee flexion was 93 degrees (80-130 degrees). Complications encountered in his series included 1 patient with deep infection, 2 patients with superficial infection and 1 patient with implant breakage.…”
mentioning
confidence: 88%
“…The presence of external rentgenonegative handle allows retrograde submuscular placing a plate and the opportunity for percutaneous fixation with monocortical self-drilling and self-tapping screws. Using unicortical (as opposed to bicortical) screws is a potential cause of loosening of screws in proximal femoral diaphysis, particularly in osteoporotic bone (39,40,41) (2)(3)(4)(5) months than the open reposition technique -an average time of 4 (3.5 -5) months . It is considered that it is preserved bone biology, fragments are not deperiostated and bone circulation is saved.…”
Section: Liss-characteristicsmentioning
confidence: 99%